Giant molluscum contagiosum mimicking a lid abscess: “Appearances can be deceptive”!! - Yamini Priya; Anupama Janardhanan (The Pan-American Journal of Ophthalmology, 2019)
Giant molluscum contagiosum (MC) is a rare nodular presentation of molluscum lesions. A diameter measuring more than half to 1 cm qualifies to be called as a giant MC. It has a strong predilection toward immunocompromised patients. A 45-year-old retropositive male presented with a large left upper eyelid swelling. After clinical evaluation, it was presumed to be a chronic lid abscess. On excision biopsy surprisingly, no purulent matter was obtained. A nodular mass was discovered which was confirmed to be giant MC on histopathology. No recurrence was found on follow-up. In immunosuppressed patients, MC has a chronic course and can rarely become large as a giant MC. CD4 lymphocytopenia and a phenomenon known as immune reconstitution inflammatory syndrome probably contribute to its pathogenesis. Giant MC must be kept in mind while evaluating an immunosuppressed patient coming with large lid swellings.